Analyzing School Budget and National Achievement Test (NAT) - Ma. Germie F. Gain; Inero V. Ancho (Jurnal Penjaminan Mutu, 2019)
This study analyzes how the allocation and utilization of school budget of selected schools in a City Schools Division in the Philippines relates with student achievement in the National Achievement Test (NAT). Data were obtained from the participating schools for school years 2012-2013 to 2014-2015 and were analyzed using Pearson correlation coefficients to determine if a relationship existed between specific school financial categories of the Annual Implementation Plan (AIP) and financial reports and the Mean Percentage Score (MPS) in NAT. Data were also analyzed through coefficients of variance to quantify the percent of the related sample that may be explained by the correlation of the variables. Findings include that training and seminar expenses, general services, repair and maintenance expenses and supplies and materials expenses were found to have a significant relationship with the MPS in NAT. Moreover, the positive relationship between financial expenditures and student performance is strongest in Mathematics, and the manner of spending financial resources only affects student performance in many subject areas but not the overall performance in NAT. These findings suggest policy recommendations that aim to guide school heads in the utilization of school budget which would most likely improve student performance in NAT.